Strategi Mengatasi Kesulitan Membaca Permulaan pada Anak Disleksia di Sekolah Dasar - Dinda Meisyah Azzahra; Adrias Adrias; Salmaini Safitri Syam (Jurnal Pendidikan, Bahasa dan Budaya, 2025)
Dyslexia is not a disorder that occurs due to a person's physical disability but rather refers to the brain that functions as a processor, dyslexia is a nerve disorder that is useful in language processing that makes sufferers have difficulty in identifying words. The purpose of this study is to identify and also describe the appropriate handling and strategies applied by educators in helping dyslexic students who have difficulty reading at the beginning with symptoms that usually occur, namely sufferers will be slow and hesitant in speaking, and difficulty in choosing the right words to express the meaning they want to convey, so the spelling method is used as a strategy to overcome it, which is a way of learning to read that starts from spelling letter by letter. The strategy of using this spelling method is indeed the most suitable to use, proven by the experience of several people who have handled dyslexic and also previous studies that present a comparison between before and after applying this method, and the results obtained show that there is a significant increase in student learning outcomes after applying this spelling method.